(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Looking through the treatises of the great medieval doctor Abu Ali Husayn ibn Abdullah ibn Sina or Avicenna (980-1037), one can find many interesting medical knowledge and advice. Separately, the doctor talks about some medicinal plants and describes their capabilities and properties. Here are some of the doctor’s observations.